A Simulation Approach for Evaluating Congestion and Its Mitigation Measures on Urban Arterials Operating with Mixed Traffic Conditions - Bari, Chintaman Santosh; Gunjal, Tanmayee V.; Dhamaniya, Ashish (Communications - Scientific Letters of the University of Zilina, 2022)
Present study evaluates the various congestion indexes in terms of speed performance index, volume to capacity ratio and congestion index based on travel time on the urban roadway network of 5.7 km in length, operating with mixed traffic conditions (traffic with varying static and dynamic characteristics of vehicles). The mitigations measures have been proposed to cater to the present traffic demand by converting the uncontrolled intersection to a partially controlled or signal-controlled intersection. In order to check the effectiveness of such mitigation measures, various scenarios have been generated in the developed and a well calibrated simulation model. It has also been observed that the speed performance index has improved by 8.88 percent while providing channelized intersection at one of the point elements and 11.52 %when the two-point elements have converted to channelizing intersection.
Keywords: congestion intersection simulation speed